Severe Hemobilia from Hepatic Artery Pseudoaneurysm - Fabio Sansonna; Stefano Boati; Raffella Sguinzi; Carmelo Migliorisi; Francesco Pugliese; Raffaele Pugliese (Case Reports in Gastrointestinal Medicine)
Background. Hemobilia is a rare, jeopardizing complication of laparoscopic cholecystectomy coming upon usually within 4 weeks after surgery. The first-line management is angiographic coil embolization of hepatic arteries, which is successful in the majority of bleedings: in a minority of cases, a second embolization or even laparotomy is needed. Case Presentation. We describe the case history of a patient in which laparoscopic cholecystectomy was complicated 3 weeks later by massive hemobilia. The cause of haemorrhage was a pseudoaneurysm of a right hepatic artery branching off the superior mesenteric artery; this complication was successfully managed by one-stage angiographic embolization with full recovery of the patient.